The Second, so called Gibš's Transport of the Czechoslovak Legions from Russia to France (1917-1918) (Theatrum historiae, 2006)
In autumn of 1917 two groups of the Czechoslovak legionaries were sent from Russia to France. They should reinforce the combat power of the „agreement“ armies on the western front. More and more they should sustain the political efforts of the leaders of the Czech and Slovak exile resistance because they needed some visual arguments for their conception of the government of the independent Czechoslovak state. Initially, the French officers watched the legionaries with suspicion and they did not trust them because the legionaries had come from the country where the Bolshevists were taking over the public power. The suspicion that the newly come soldiers were ideologically influenced by the Bolshevists was rather based upon the specific relations among the legionary troops. The officers in these forces did not create tight walls between them and their rank and file and they did not demand tough discipline as it was ordinary in the French and other armies. But the very excellent results in the training and in the fight persuaded the French commanders to change their initial opinion. They discovered that the legionaries were perfect soldiers with the high combat morals which originated from the clear aim: they wished to destroy the Habsburg monarchy and create the independent Czechoslovakia.